2020
DOI: 10.1016/j.jtcvs.2019.12.115
|View full text |Cite
|
Sign up to set email alerts
|

Routine surveillance for diagnosis of venous thromboembolism after pleurectomy for malignant pleural mesothelioma

Abstract: Objective-The purpose of this study was to determine the incidence of venous thromboembolism and utility of a routine surveillance program in patients undergoing surgery for mesothelioma.Methods-Patients undergoing pleurectomy from May 2016 to August 2018 were included. A standardized surveillance program to look for venous thromboembolism in this group included noninvasive studies every 7 days postoperatively or earlier if symptomatic. All patients received external pneumatic compression sleeves in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Interestingly, the rate of symptomatic deep venous thrombosis at 8.8% (3/34) in this study is lower than recently reported data for pleurectomy and decortication of mesothelioma alone, 19.4% (18/93) 18 . This lower rate is despite the lack of chemotherapy use and different tumor biology.…”
Section: Discussioncontrasting
confidence: 76%
“…Interestingly, the rate of symptomatic deep venous thrombosis at 8.8% (3/34) in this study is lower than recently reported data for pleurectomy and decortication of mesothelioma alone, 19.4% (18/93) 18 . This lower rate is despite the lack of chemotherapy use and different tumor biology.…”
Section: Discussioncontrasting
confidence: 76%
“…Alteration in surgical technique from EPP to PD [59] 3. Decreasing perioperative complications by implementing strategies to minimize occurrences of deep vein thrombosis (DVT) and pulmonary embolism (PE) through routine surveillance measures and early detection of nonclinical events [57]. Additionally, addressing issues like prolonged air leaks and empyema by meticulously repairing all lung lacerations by stapling or over-sewing with sutures [68], and prioritizing primary repair of the diaphragm whenever feasible, avoiding resection and reconstruction with a prosthetic patch [55].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, as many as 33% of patients with deep vein thrombosis were asymptomatic at the time of diagnosis. De Leon et al suggested that routine surveillance could be beneficial in identifying and managing deep vein thrombosis before it advances to symptomatic or fatal pulmonary embolus [57].…”
Section: Pleurectomy Decorticationmentioning
confidence: 99%